Design a personalised product service system utilising a multi-agent system. (January 2020) - Chiu, Ming-Chuan; Tsai, Chi-Hsuan
Abstract: To help achieve sustainability, reduce the risk of uncertainty, and fulfil a variety of customer needs, the concept of a Product Service System has evolved for use as a business model. While previous studies have addressed PSS development, there is yet no dynamic methodology enabling a PSS to adjust quickly to external changes and customer response. With that gap in mind, this paper presents a Multi-Agent-based Personalised Product Service System (MAPPSS) system. MAPPSS provides a reliable method for analysis which is applicable in various pervasive environments. With this proposed system, users are able to select expected service characteristics, after which service composition is conducted by selecting related products and services from a database. In a comparison of existing systems using different scenarios, we show that customer acceptance, energy utilization, and product utilization generate a two-digit improvement with the proposed system, while profit and costs may increase slightly. When using the proposed method, the competence of an enterprise can be enhanced as a result of these user-oriented features. The performance monitoring and iterating elements of the system allow an almost immediate improvement in the generated PSS.